2019
DOI: 10.3920/wmj2018.2354
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate management of complementary foods contributes to the risk of aflatoxin exposure and low nutrition status among children

Abstract: Early exposure to aflatoxins through complementary food is linked to impaired growth in childhood. The current study assessed the household’s practices on management of complementary foods in relation to the risk of aflatoxin exposure and poor nutritional status among infant and young children in Tanzania. A cross-sectional study of complementary feeding practices, aflatoxin exposure and nutritional status was conducted to 101 infants and young children aged between 6-23 months in Dodoma region of Tanzania. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 35 publications
3
32
0
1
Order By: Relevance
“…Twelve percent of the samples exceeded the Tanzanian limit (10 µg/kg) for total AFs. In another study in Dodoma region of Tanzania, Makori et al (2018) reported AFB1 contamination in 42.5% of complementary flours. The levels ranged from 0.25 to 2,128.1 µg/kg.…”
Section: Nature and Toxicity Of Aflatoxinsmentioning
confidence: 94%
See 4 more Smart Citations
“…Twelve percent of the samples exceeded the Tanzanian limit (10 µg/kg) for total AFs. In another study in Dodoma region of Tanzania, Makori et al (2018) reported AFB1 contamination in 42.5% of complementary flours. The levels ranged from 0.25 to 2,128.1 µg/kg.…”
Section: Nature and Toxicity Of Aflatoxinsmentioning
confidence: 94%
“…Maternal and caregiver unawareness about the problem of mycotoxin contamination in maize and inadequate knowledge about appropriate complementary feeding are the main reasons for the early introduction of maize-based complementary food in Tanzania. In a study conducted in Dodoma Tanzania, awareness of adequate practices for IYC feeding among parents was found to be 35% (Makori et al, 2018). Generally, extension services on child feeding are inadequate and rare.…”
Section: Main Determinants Of Af and Fb Exposures In Tanzanian Childrenmentioning
confidence: 99%
See 3 more Smart Citations